2014
DOI: 10.1002/anie.201310211
|View full text |Cite
|
Sign up to set email alerts
|

Azobenzene‐Functionalized Metal–Organic Polyhedra for the Optically Responsive Capture and Release of Guest Molecules

Abstract: Stimuli-responsive metal-organic polyhedra (srMOPs) functionalized with azobenzene showed UV-irradiation-induced isomerization from the insoluble trans-srMOP to the soluble cis-srMOP, whereas irradiation with blue light reversed this process. Guest molecules were trapped and released upon cis-to-trans and trans-to-cis isomerization of the srMOPs, respectively. This study provides a new direction in the ever-diversifying field of MOPs, while laying the groundwork for a new class of optically responsive material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
132
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(134 citation statements)
references
References 50 publications
0
132
0
2
Order By: Relevance
“…The E → Z photoisomerization of azobenzene derivatives is well documented for azobenzenecontaining polymers 18 , liquid crystals 9,18-24 , thin films [25][26][27] and crystals at the solid-liquid interface 28 , and a limited number of examples are reported in porous materials [29][30][31][32][33] (for example, metal-organic and covalent organic frameworks) and in molecular crystalline forms in which the azobenzene moiety is functionalized with polar substituents [34][35][36] . Our strategy is based on the use of molecules containing a central node that imparts a star-like threedimensional arrangement to azobenzene moieties for the fabrication of molecular crystals endowed with permanent porosity capable of promoting reversible E/Z isomerization in the solid state.…”
mentioning
confidence: 98%
“…The E → Z photoisomerization of azobenzene derivatives is well documented for azobenzenecontaining polymers 18 , liquid crystals 9,18-24 , thin films [25][26][27] and crystals at the solid-liquid interface 28 , and a limited number of examples are reported in porous materials [29][30][31][32][33] (for example, metal-organic and covalent organic frameworks) and in molecular crystalline forms in which the azobenzene moiety is functionalized with polar substituents [34][35][36] . Our strategy is based on the use of molecules containing a central node that imparts a star-like threedimensional arrangement to azobenzene moieties for the fabrication of molecular crystals endowed with permanent porosity capable of promoting reversible E/Z isomerization in the solid state.…”
mentioning
confidence: 98%
“…6 Metal-organic frameworks (MOFs) are a class of multidimensional porous networks composed of organic struts and inorganic nodes, and can be systematically tuned in terms of chemical composition and precise arrangement. [10][11][12] These studies have focused extensively on azobenzene frameworks, [13][14][15][16][17][18][19] as well as on diarylethenes 20,21 and others. [10][11][12] These studies have focused extensively on azobenzene frameworks, [13][14][15][16][17][18][19] as well as on diarylethenes 20,21 and others.…”
mentioning
confidence: 99%
“…That is to say because the biting angles between the acpy ligands and the [{Re(CO) 3 } 6 (bho)] nodes are flexible, the MB-1 molecule exhibits a dynamic behavior in the open and closed forms (Figure 3 c). [16] Further analysis of this structure indicated that these MB-1 units in 1' are merely attached to each other in a head-to-tail manner and not mutually interlocking at all. The structural differences between 1 and 1' was also shown when compound 1 was heated under reflux in 1,3,5-mesitylene, these interlocking MB-1 units were completely disassembled, and then can further self-assemble and crystalize as compound 1'.…”
Section: Hexaolate Complexesmentioning
confidence: 94%